The High-Energy Protons of the Ground Level Enhancement (GLE74) Event on 11 May 2024 - Papaioannou, Athanasios; Mishev, Alexander; Usoskin, Ilya; Heber, Bernd; Vainio, Rami; Larsen, Nicholas; Jarry, Manon; Rouillard, Alexis; Talebpour Sheshvan, Nasrin; Laurenza, Monica; Dumbovi, Mateja; Vasalos, Georgios; et al. (SPRINGER, 2025)
High energy solar protons were observed by particle detectors aboard spacecraft in near-Earth orbit on May 11, 2024 and produced the 74th ground level enhancement (GLE74) event registered by ground-based neutron monitors. This study involves a detailed reconstruction of the neutron monitor response, along with the identification of the solar eruption responsible for the emission of the primary particles, utilizing both in situ and remote-sensing. Observations spanning proton energies from a few MeV to around 1.64 GeV, collected from the Solar and Heliospheric Observatory (SOHO), the Geostationary Operational Environmental Satellite (GOES), the Solar Terrestrial Relations Observatory (STEREO-A), and neutron monitors, were integrated with records of the associated solar soft X-ray flare, coronal mass ejection, and radio bursts, to identify the solar origin of the GLE74. Additionally, a time-shift analysis was conducted to link the detected particles to their solar sources. Finally, a comparison of GLE74 to previous ones is carried out. GLE74 reached a maximum particle rigidity of at least 2.4 GV and was associated with a series of type III, type II, and type IV radio bursts. The release time of the primary solar energetic particles (SEPs) with an energy of 500 MeV was estimated to be around 01:21 UT. A significant SEP flux was observed from the anti-Sun direction with a relatively broad angular distribution, rather than a narrow, beam-like pattern, particularly during the main phase at the particle peak flux. Comparisons with previous GLEs suggest that GLE74 was a typical event in terms of solar eruption dynamics.